PENGARUH LIKUIDITAS, PROFITABILITAS, DAN LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN SUB SEKTOR FARMASI DI BURSA EFEK INDONESIA PERIODE 2018-2022 - Annisa, Lydya Nur (Income, 2024)
This research aims to find out and explain how the effect of current ratio (CR), Return on Assets (ROA), dan Debt to Equity Ratio (DER) on stock prices in pharmaceutical subsector companies listed on the Indonesia Stock Exchange (IDX). The object of this research is a pharmaceutical subsector company listed on the Indonesia Stock Exchange (IDX) for the period 2018-2022 with a sample number of 9 companies. The study used purposive sampling techniques. Data used secondary data. Data analysis techniques use descriptive statistical analysis and multiple linear regression analysis. The results of the hypothesis test proved the Current ratio (CR), Return on Assets (ROA), dan Debt to Equity Ratio (DER) had an influence on the share price of pharmaceutical subsector companies listed on the IDX for the period 2018-2022. Variable current ratio (CR) has a negative influence on the stock price of pharmaceutical subsector companies. Return on Assets (ROA) has no effect on the stock price of pharmaceutical subsector companies. Debt to Equity Ratio (DER) has a negative influence on the stock price of pharmaceutical subsector companies.